Influence of Nitrogen Addition Levels on N2O Flux and Yield of Spring Wheat in the Loess Plateau - Haiyan Wang; Jiangqi Wu; Guang Li; Jianyu Yuan (Agronomy, 2025)
Nitrogen fertilizer plays a crucial role in enhancing soil fertility, impacting both crop yields and nitrous oxide (N2O) emissions from farmland soils. However, while nitrogen fertilizers increase yields, they also influence N2O emissions, and this relationship remains understudied in the Loess Plateau region of China. This study examined the effect of four nitrogen fertilizer levels—no nitrogen (CK), low (LN), medium (MN), and high (HN)—on N2O emissions and spring wheat yield. Over two years, nitrogen fertilization significantly increased N2O emissions, with HN treatment resulting in emissions 229.95%, 69.38%, and 46.52% higher than CK, LN, and MN, respectively. Emission fluxes exhibited strong seasonal variability, influenced by soil temperature, enzyme activity, and nitrogen availability. Spring wheat yields initially increased and then decreased, with the highest yields recorded under MN treatment (1283.67 and 1335.83 kg·ha−1). Given the sharp rise in N2O emissions due to nitrogen application in arid areas, the contribution of spring wheat soil to global warming and ozone depletion cannot be overlooked. Results suggest that a moderate nitrogen application of 110 kg·ha−1 in the Loess Plateau optimizes yield, enhances soil conditions, and mitigates N2O emissions, whereas excessive nitrogen leads to nitrate accumulation, exacerbating environmental issues like the greenhouse effect, and ultimately reducing wheat yield and causing economic losses.